KONTRIBUSI ISTRI NELAYAN JUBI TERHADAP EKONOMI KELUARGA DI KELURAHAN BATULUBANG KECAMATAN LEMBEH SELATAN KOTA BITUNG - Josua Amy Hamel; Florence V. Longdong; Olvie V. Kotambunan; Jardie A. Andaki; Christian R. Dien; Grace O. Tambani (Universitas Sam Ratulangi, 2023)
Abstract The purpose of this study is to determine the contribution of income and source of income from the wife of a nelayan jubiâ€ in Batulubang Village. This type of research is descriptive with a sampling method of data collection. The respondent was the wife of a nelayan jubiâ€ who contributed to the family. The data was taken from 16 respondents who were fishermen's wives who had side jobs other than being housewives. The sampling method chosen is purposive sampling with its limitations. Has the age of under 60 years and as a fisherman's wife has been running a business for more than 1 year and the husband's length of time as a jubi fisherman is not less than 3 years. Based on the results of the study, it can be concluded that the work of the wife of a â€œnelayan jubiâ€ in Batulubang Village, South Lembeh District, Bitung City, is a business selling garden products, a business selling credit, a fish seller business, a food stall business, a beverage selling business, a housekeeper, a sound system business and a stall business. The average contribution of jubi fishermen's wife's income to the family economy is 18.81% of the total family income of Rp5,015,750 per month. Â Keywords: contribution; fisherman's wife; â€œnelayan jubiâ€ Â Abstrak Tujuan penelitian ini adalah untuk mengetahui kontribusi pendapatan dan sumber pendapatan dari istri nelayan jubi di Kelurahan Batulubang. Jenis penelitian adalah deskriptif dengan metode pengumpulan data secara sampling. Responden merupakan istri nelayan jubi yang memberi kontribusi terhadap keluarga. Data diambil dari 16 responden yang merupakan istri nelayan yang memiliki pekerjaan sampingan selain menjadi ibu rumah tangga. Metode sampling yang dipilih adalah purposive sampling dengan batasannya. Memiliki umur dibawah 60 tahun dan sebagai istri nelayan telah menjalankan usaha lebih dari 1 tahun dan lama suami menjadi nelayan jubi tidak kurang dari 3 tahun. Berdasarkan hasil penelitian, dapat disimpulkan bahwa pekerjaan istri nelayan jubi di Kelurahan Batulubang Kecamatan Lembeh Selatan Kota Bitung yaitu usaha jual hasil kebun, usaha jual pulsa, usaha penjual ikan, usaha warung makan, usaha jualan minuman, pembantu rumah tangga, usaha sound system dan usaha warung. Rata-rata kontribusi pendapatan istri nelayan jubi terhadap ekonomi keluarga sebesar 18,81% dari total pendapatan keluarga yang sebesar Rp5.015.750 per bulan. Kata Kunci: kontribusi; istri nelayan; nelayan jubi